2017
DOI: 10.1353/nib.2017.0046
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Challenges for Patient Access to Physical Therapy: Views of Staff Members from Three Publicly–Funded Outpatient Physical Therapy Departments

Abstract: Demographic change and changing population needs are important drivers of increased demand for rehabilitation. These developments place significant stress on access to physical therapy services, as current resources are insufficient to meet the growing demand. This situation presents ethical challenges for physical therapists and others involved in managing wait lists and prioritizing access to services. The purpose of this study is to explore how outpatient physical therapy department (OPD) staff experience e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
0
18
0
3
Order By: Relevance
“…Our results are consistent with those of recent studies of the practices in Quebec PT outpatient departments, where physiotherapists with managerial responsibilities and administrative staff decide how to prioritize access for people on the waiting list, whereas physiotherapists decide on frequency and duration of treatment for their patients. 1,49 Figure 3 Importance of factors associated with making decisions about treatment duration, according to respondents working in either the private or the public sector. This advance online version may differ slightly from the final published version.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those of recent studies of the practices in Quebec PT outpatient departments, where physiotherapists with managerial responsibilities and administrative staff decide how to prioritize access for people on the waiting list, whereas physiotherapists decide on frequency and duration of treatment for their patients. 1,49 Figure 3 Importance of factors associated with making decisions about treatment duration, according to respondents working in either the private or the public sector. This advance online version may differ slightly from the final published version.…”
Section: Discussionmentioning
confidence: 99%
“…These barriers were related to the lack of compatibility with actual prioritization practice and lack of common vision about prioritization, which were highlighted in our study. The complexity of the implementation can be partly explained by the fact that patient prioritization in waiting lists is a decision which encompasses ethical challenges [60,61]. Having a common vision about prioritization in a team, such as in a rehabilitation program, can lead to a clash of values related to equity.…”
Section: Discussionmentioning
confidence: 99%
“…care [61]. Laliberté et al [61] suggested to improve training and combine with research on evidence-based practices to document current weaknesses, and to identify waiting list management procedures that can make resource allocation decisions more equitable and transparent.…”
Section: Discussionmentioning
confidence: 99%
“…While the results of our survey indicate that a majority of outpatient physiotherapy departments in Québec used the diagnosis as their most important criterion to prioritize referrals, level of acuity was also frequently considered. Furthermore, in many settings, postoperative conditions were systematically prioritized over chronic conditions, thus compromising access to physiotherapy for the latter [21]. Studies from Ontario and Australia found that the most frequent prioritization criterion for physiotherapy was the acuity of the condition.…”
Section: Leaving Chronic Patients Behindmentioning
confidence: 99%